Between Autonomy and Independence. The Democratisation of the Armed Forces in Latin America in the Twenty-First Century - Stelmach, Michał (International Studies. Interdisciplinary Political and Cultural Journal, 2020)
The aim of this article is to analyse the new forms of militarism as well as the position and the role of the armed forces in Latin American political systems in the twenty-first century. The first part analyses two selected forms of military participation in politics: the participation of former servicemembers in presidential elections and their performance as presidents, and the militarisation of political parties. The second part of the article focuses on the issue of contemporary civil-military relations in Latin America, discussing the problems associated with the establishment of democratic control over the armed forces, the reform of the Ministries of Defense and the redefinition of the functions of the army.